Diagnostic dilemma in acute neurological presentation of spinal arachnoid cysts: A case report - Jain, Swati; Sun, Ira; Pang, Boon Chuan; Lim, Su Lone; Low, Shiong Wen (Frontiers in Surgery, 2023)
BACKGROUND Spinal arachnoid cysts are relatively uncommon cerebrospinal fluid filled sacs formed by arachnoid membranes which can be either idiopathic or acquired. The neurological presentation of these cysts is varied. Advancements in imaging techniques have allowed improved characterization of these entities as well as excluding other possible causes of the clinical presentation. Their presentation remains varied ranging from pain to progressive neurological deficit. We present 2 case reports of patients with thoracic arachnoid cyst that posed diagnostic dilemma during the initial presentation due to acute neurology and their eventual recovery after surgical intervention. CASE DESCRIPTION First case is of a patient with end stage renal failure that prevented administration of contrast during work up. The differential diagnosis varied from intradural abscess versus an arachnoid cyst. The second patient presented with non-remitting back pain which progressed to acute neurological deficit. Both patients recovered well after decompression of the cyst. CONCLUSION Relatively benign nature and lack of understanding of the temporal presentation of neurological symptoms, decision to intervene still is patient dependent and extent of neurological deterioration at time of presentation. Surgical intervention results in rapid and near complete reversal of neurological symptoms. However, further studies need to be done to understand the acute presentation of these cysts which are apparently long standing.